Discoursing the use of complementary therapy for cancer care in Indonesia: A perspective - Elisa Rinihapsari; Yohanes Budi Widianarko; Margaretha Sih Setya Utami (Universitas Muhammadiyah Magelang, 2022)
The use of CAM in Indonesia is relatively high, but this method is still considered a second-class treatment. There are still many modern medical practitioners who have not accepted this method as a method of treatment that can be accounted for. This article attempts to explain why complementary-alternative medicine continues to develop and why it needs to be widely proposed as a treatment method of choice, in addition to modern medical treatment. Conventional medical medicine or modern medicine and complementary-alternative medicine have different philosophical foundations, so imposing an assessment using biomedical methods to prove the efficacy of CAM seems less appropriate. Suppose evidence of efficacy is required for CAM to be accepted. In that case, it seems that research methods with qualitative and anthropological approaches should be chosen that provide more space for individual experiences in the use of CAM. Keywords: complementary and alternative medicine; modern medicine; discourse, biomedical; anthropology